2008
DOI: 10.1083/jcb.200711066
|View full text |Cite
|
Sign up to set email alerts
|

E2-25K/Hip-2 regulates caspase-12 in ER stress–mediated Aβ neurotoxicity

Abstract: Amyloid-β (Aβ) neurotoxicity is believed to contribute to the pathogenesis of Alzheimer's disease (AD). Previously we found that E2-25K/Hip-2, an E2 ubiquitin-conjugating enzyme, mediates Aβ neurotoxicity. Here, we report that E2-25K/Hip-2 modulates caspase-12 activity via the ubiquitin/proteasome system. Levels of endoplasmic reticulum (ER)–resident caspase-12 are strongly up-regulated in the brains of AD model mice, where the enzyme colocalizes with E2-25K/Hip-2. Aβ increases expression of E2-25K/Hip-2, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 36 publications
1
57
0
Order By: Relevance
“…We next assessed ER stress responses. In murine neurons, A␤ 42 activates both calpains and ER-associated caspase-12 (20). The human homolog of caspase-12 has a frameshift mutation resulting in a premature stop codon and an amino acid substitution within a critical site for caspase enzymatic activity, rendering it catalytically inactive (21).…”
Section: Chronic C16:0 Paf Accumulation Induces An Er Stress-dependentmentioning
confidence: 99%
“…We next assessed ER stress responses. In murine neurons, A␤ 42 activates both calpains and ER-associated caspase-12 (20). The human homolog of caspase-12 has a frameshift mutation resulting in a premature stop codon and an amino acid substitution within a critical site for caspase enzymatic activity, rendering it catalytically inactive (21).…”
Section: Chronic C16:0 Paf Accumulation Induces An Er Stress-dependentmentioning
confidence: 99%
“…Conversely, overexpressed FcγRIIb, but not the I232T FcγRIIb mutant, induced similar ER stress responses in HT22 cells (Supplemental Figure 5D). Of particular note, Aβ 1-42 -induced activation of caspase-12, a key player in ER stress-and Aβ-mediated apoptosis (12,31), was abrogated in Fcgr2b KO cortical neurons (Supplemental Figure 5C). Furthermore, ectopic expression of the caspase-12 active site mutant (C298S) significantly suppressed FcγRIIb-mediated HT22 cell death, while caspase-12 significantly enhanced it (Supplemental Figure 5E).…”
Section: Induction Of Fcγriib Expression In Neurons Incubated With Aβmentioning
confidence: 99%
“…We previously isolated a cytosolic mediator of Aβ neurotoxicity, E2-25K/Hip-2, based on a global analysis of the genes expressed in the primary cortical neurons exposed to Aβ (11,12). Using the same approach, we found that Aβ strongly upregulated the expression of FcγRIIb in the cortical neurons.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…PERK and phosphorylated eIF2α were also upregulated [134,135] and there was a decrease in Sigma-1R [136]. Amyloid β increases PERK activation and CHOP expression in neurons in culture [137][138][139]. Expression of mutant presenilin 1, linked to familial AD, also alters the PERK, IRE1 and ATF6 pathways [140,141] and increases CHOP expression [142].…”
Section: Er Stress In Neurodegenerative Diseasesmentioning
confidence: 99%